2016
DOI: 10.1002/jgm.2886
|View full text |Cite
|
Sign up to set email alerts
|

The neuropilin‐1 receptor mediates enhanced tumor delivery of H2K polyplexes

Abstract: Background Promising plasmid-based treatments have limited value without an effective delivery system. Recently, the linear H2K with a repeating –KHHK pattern was determined to be an effective plasmid carrier to tumor xenografts in vivo. Although unpacking of the H2K polyplex within the tumor may have a role, the mechanism for the enhanced efficacy remains unclear. Methods After solid-phase synthesis of linear and branched histidine-lysine (HK) peptide carriers of plasmids, the peptides were compared for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Under these conditions, however, it is also possible that excess NPs may enter by a less preferred endocytic pathway. Although recent studies with TPP-labeled silver particles or proteins showed that these enter only by the NRP1-mediated endocytosis (39), polyplexes, which are dependent on NRP1 for widespread distribution in the tumor, enter cells (at least in vitro ) through numerous endocytic pathways (16). How much NRP1 receptor mediated therapy is limited by saturation of receptors on tumor cells may be dependent on multiple factors including the specific TPP-drug (or NP) conjugate, the pegylation pattern, and the level of non-NRP1 mediated endocytosis in the cell.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Under these conditions, however, it is also possible that excess NPs may enter by a less preferred endocytic pathway. Although recent studies with TPP-labeled silver particles or proteins showed that these enter only by the NRP1-mediated endocytosis (39), polyplexes, which are dependent on NRP1 for widespread distribution in the tumor, enter cells (at least in vitro ) through numerous endocytic pathways (16). How much NRP1 receptor mediated therapy is limited by saturation of receptors on tumor cells may be dependent on multiple factors including the specific TPP-drug (or NP) conjugate, the pegylation pattern, and the level of non-NRP1 mediated endocytosis in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sugahara et al determined that levels of a doxorubicin conjugate or an NP such as Abraxane accumulated in tumors significantly more with TPP-targeting (7). Still, EPR and/or tumor interstitial pressure may have a role in tumor targeting and biodistribution of molecules mediated by TPP targeting of NRP1 (16, 44). For instance, in addition to targeting NRP1, EPR may provide a necessary component for the increased accumulation of polyplexes that did not contain a targeting ligand (15, 16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations